Functional Flexibility of Intestinal IgA – Broadening the Fine Line - Slack, Emma; Balmer, Maria L.; Fritz, Jörg H.; Hapfelmeier, Siegfried (Frontiers in Immunology, 2012)
Intestinal bacteria outnumber our own human cells in conditions of both health and disease. It has long been recognized that secretory antibody, particularly IgA, is produced in response to these microbes and hypothesized that this must play an important role in defining the relationship between a host and its intestinal microbes. However, the exact role of IgA and the mechanisms by which IgA can act are only beginning to be understood. In this review we attempt to unravel the complex interaction between so-called “natural”, “primitive” (T-cell-independent) and “classical” IgA responses, the nature of the intestinal microbiota/intestinal pathogens and the highly flexible dynamic homeostasis of the mucosal immune system. Such an analysis reveals that low-affinity IgA is sufficient to protect the host from excess mucosal immune activation induced by harmless commensal microbes. However, affinity-maturation of “classical” IgA is essential to provide protection from more invasive commensal species such as segmented filamentous bacteria and from true pathogens such as Salmonella typhimurium. Thus a correlation is revealed between “sophistication” of the IgA response and aggressiveness of the challenge. A second emerging theme is that more invasive species take advantage of host inflammatory mechanisms to more successfully compete with the resident microbiota. In many cases, the function of IgA may be to limit such inflammatory responses, either directly by coagulating or inhibiting virulence of bacteria before they can interact with the host or by modulating immune signaling induced by host recognition. Therefore IgA appears to provide an added layer of robustness in the intestinal ecosystem, promoting “commensal-like” behavior of its residents.